2020
DOI: 10.1136/annrheumdis-2020-eular.5010
|View full text |Cite
|
Sign up to set email alerts
|

Op0277 aurora Phase 3 Study Demonstrates Voclosporin Statistical Superiority Over Standard of Care in Lupus Nephritis (Ln)

Abstract: Background:Voclosporin (VCS) is a novel high potency calcineurin inhibitor (CNI) with a favorable metabolic profile and a consistent predictable dose response potentially eliminating the need for therapeutic drug monitoring. LN occurs more frequently and is more severe in Hispanic/Latino ethnicity SLE patients. The recently completed phase 3 AURORA study builds on the favorable efficacy seen in the Phase IIb AURA-LV study in patients with active LN.Objectives:Document efficacy and safety of VCS vs placebo over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 0 publications
0
26
0
1
Order By: Relevance
“…85 A subsequent phase 3 study recently confirmed superior efficacy without safety concerns (still in abstract form). 86 In reference to biologics, new studies have confirmed earlier data on the efficacy of belimumab. In patients with SLE from…”
Section: Recent Clinical Trials: Paving the Way For The Futurementioning
confidence: 62%
“…85 A subsequent phase 3 study recently confirmed superior efficacy without safety concerns (still in abstract form). 86 In reference to biologics, new studies have confirmed earlier data on the efficacy of belimumab. In patients with SLE from…”
Section: Recent Clinical Trials: Paving the Way For The Futurementioning
confidence: 62%
“…More deaths were noticed in the low-dose regimen (11.2%) compared to the high-dose regimen (2.3%) or the placebo group (1.1%). A phase 3 study showed that the addition of voclosporin to mycophenolate mofetil and low-dose corticosteroids was superior to standard treatment in patients with lupus nephritis (44). The AURORA study included 357 patients with active lupus nephritis.…”
Section: Selective Inhibition Of Intracellular Biochemical Pathways Cmentioning
confidence: 99%
“…VOC is a more potent CNI than cyclosporine A, has more predictable pharmacodynamics (thereby avoiding repeated drug monitoring), and presents a faster elimination of metabolites (thereby is likely less responsible for adverse events). In a phase 2 (AURA) and a phase 3 trial (AURORA), where steroids were very promptly tapered, it was shown that, compared to MMF alone, the combination of MMF and VOC induced a higher CRR at 6 and 12 months (in the AURA trial, 27.3% versus 32.6% and in the AURORA trial, 22.5% versus 40.8%, in the two groups, respectively) [53][54][55]. Despite these results being clinically significant and obtained without additional serious adverse events, most likely leading to labeling of VOC for LN by the medical agencies in the next months, some caveats must be addressed.…”
Section: Combination Therapymentioning
confidence: 99%